1990
DOI: 10.1007/bf02205560
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Ro (SSA)/La (SSB) antibodies and Sjögren's syndrome

Abstract: Antibodies to Ro (SSA) and La (SSB) cellular ribonucleoprotein complexes are found in the circulation of patients with Sjögren's syndrome (SS), mainly in those with the primary form of the syndrome. Their presence is associated with long disease duration, earlier disease onset, parotid gland enlargement, systemic manifestations and also with hypergammaglobulinemia, rheumatoid factors and monoclonal type II cryoglobulins. While anti-Ro (SSA) antibodies are not specific for SS, anti-La (SSB) antibodies seem to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 31 publications
2
15
0
1
Order By: Relevance
“…Clinically, SS manifests as sicca symptoms on mucosal surfaces, including oral and ocular dryness due to the destruction of secretory glands by lymphocytic foci with T cells and B cells . Serologically, the most notable autoantibodies are those recognizing antinuclear antigens (ANAs), RNP complexes (Ro/SSA and La/SSB), and type 3 muscarinic acetylcholine receptors (M3Rs) .…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, SS manifests as sicca symptoms on mucosal surfaces, including oral and ocular dryness due to the destruction of secretory glands by lymphocytic foci with T cells and B cells . Serologically, the most notable autoantibodies are those recognizing antinuclear antigens (ANAs), RNP complexes (Ro/SSA and La/SSB), and type 3 muscarinic acetylcholine receptors (M3Rs) .…”
Section: Introductionmentioning
confidence: 99%
“…The severity of the lip biopsy results does not correlate well with disease activity or clinical symptoms 8 . In contrast, saliva flow rate is more closely correlated with the presence of ANA and anti‐SS‐A antibodies than with lip biopsy results 22 . In addition, the final diagnosis can change in up to 53% of cases when a second evaluation of the same labial salivary gland biopsy specimen is done 23 .…”
Section: Discussionmentioning
confidence: 99%
“…8 In contrast, saliva flow rate is more closely correlated with the presence of ANA and anti-SS-A antibodies than with lip biopsy results. 22 In addition, the final diagnosis can change in up to 53% of cases when a second evaluation of the same labial salivary gland biopsy specimen is done. 23 Recent animal studies showed that lacrimation and salivation are not related to lymphocytic infiltration of the lacrimal and salivary glands, 24 and that dysfunction in secretion is mediated by antimuscarinic acetylcholine receptor antibody.…”
Section: Discussionmentioning
confidence: 99%
“…IgG, IgM, or IgA autoantibodies against ductal cell ribonucleotides, called SSA (Ro) and SSB (La), which appear to be dimers of 52 and 65 kDa, are found in SS but do not appear to be responsible for tissue destruction (Moutsopoulos and Zerva, 1990) and do not correlate with focal sialadenitis. Patients with primary disease show an increased association with HLA-DW3 and the P2X7 receptor (Lester et al, 2013).…”
Section: Pathogenesismentioning
confidence: 98%